l-Ascorbic acid metabolism in parthenocarpic and seeded cherry tomatoes - Tsaniklidis, Georgios; Delis, Costas; Nikoloudakis, Nikolaos; Katinakis, Panayotis; Passam, Harold Christopher; Aivalakis, Georgios (My University, 2014)
The auxin treatment in tomato plants during anthesis has been extensively used for setting fruits in adverse climatic conditions (e.g., low temperatures and inadequate light), which is well known that reduces pollen availability and fertility. Since auxin application may affect fruit composition and quality, we examined l-ascorbic acid metabolism in seeded fruit (set by natural pollination) and parthenocarpic fruit (set by auxin) in cherry tomato cv. Conchita. Specifically, we studied the oxidized and total ascorbic acid contents, the expression of all characterized genes of l-ascorbic acid metabolism, the activity of ascorbate peroxidase and dehydroascorbate reductase and the immunolocalization of ascorbate peroxidase. Differences were detected between seeded and parthenocarpic fruits, in the expression of some of the genes of ascorbic acid metabolism. However, strong presence of l-ascorbic acid peroxidase protein was detected on the developing seeds. Our data indicate that induced parthenocarpy in auxin treated plants has a significant influence in ascorbic acid metabolism comparing to seeded tomato fruits. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Ascorbate peroxidase; Ascorbic acid; Dehydroascorbate reductase; Monodehydroascorbate reductase; Parthenocarpy; Tomato